2010
DOI: 10.1097/sap.0b013e3181c47ef4
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinous Muscle Flap Reconstruction of Complex Midline Back Wounds

Abstract: With increasingly complex spine surgeries now being performed on a more comorbid patient population, the reconstruction of midline back wounds from these procedures is becoming a frequent dilemma encountered by plastic surgery. The purpose of this study is to examine the effect of various preoperative risk factors on postoperative wound healing complications after paraspinous muscle flap reconstruction of midline back defects. An Institutional Review Board-approved, 11-year, retrospective, office and hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 33 publications
(24 reference statements)
3
58
0
Order By: Relevance
“…Our PubMed search yielded 532 articles for screening, and, with the application of our inclusion criteria, we narrowed down the results to 17 articles (3 case reports, 8,14,21 5 case series, 4,9,16,20,30 and 9 retrospective studies 7,10,13,17,[24][25][26]28,32 ). The detailed study selection flowchart is shown in Fig.…”
Section: Results Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our PubMed search yielded 532 articles for screening, and, with the application of our inclusion criteria, we narrowed down the results to 17 articles (3 case reports, 8,14,21 5 case series, 4,9,16,20,30 and 9 retrospective studies 7,10,13,17,[24][25][26]28,32 ). The detailed study selection flowchart is shown in Fig.…”
Section: Results Search Resultsmentioning
confidence: 99%
“…7,13,17,25 A total of 262 patients were pooled to analyze the overall breakdown of various potential contributing factors. The greatest potential factor was involvement of instrumentation (77.6%).…”
Section: Risk Factors For the Development Of Postoperative Woundsmentioning
confidence: 99%
“…2 Other muscles such as paraspinal muscles and gluteus muscle flaps can be used to reconstruct the lower back. 3 However, large defects often require multiple local muscle flaps to achieve adequate coverage, and risks in increased possibility for donor site morbidity. 2,4 Free flaps may be inevitable for extensive defects but finding adequate recipient vessels remains to be challenging and alternative methods, such as arteriovenous looping and interposition grafts may increase the risk for complication.…”
mentioning
confidence: 99%
“…Except for the thoracolumbar area in the patient with MMC, the monofilament test showed a threshold of 3.61 in all reconstructed areas, indicating that protective sensibility was obtained in these areas. The average hospital stay after wound closure was 10 days (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. During the follow-up period (mean 65 mo, range 7-106) 1 patient developed an infection in the operated area 81 months postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…Mericli et al showed in a large series of patients that the removal of the instrumentation may actually impede healing in the reconstructed area. 15 In all patients except the 1 with cancer, the wounds were treated with VAC after debridement until the results of bone cultures were known. The VAC system has been reported to be an effective adjunct in wound conditioning and closure of these complex wounds.…”
Section: Discussionmentioning
confidence: 99%